Photoluminescence and structural properties of silicon nanostructures grown by layer-by-layer deposition - Tong, G.B.; Muhamad, M.R.; Rahman, S.A. (2012)
In this study, silicon nanostructures were synthesized by layer-by-layer (LBL) method using the radio-frequency plasma enhanced chemical vapor deposition (rf PECVD) technique. The influence of the substrate temperature on the morphological, structural and photoluminescence properties of these nanostructures were investigated using field emission scanning electron microscope (FESEM), high resolution transmission electron microscope (HRTEM), Micro-Raman scattering spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and photoluminescence (PL) spectroscopy. The results revealed that the LBL deposition resulted in the formation of aggregates of nanocrystalline Si (nc-Si) grains with very small crystallites of a size of less than 3 nm embedded in a mixed phase of hydrogenated amorphous silicon and amorphous silicon oxide matrix. The nc-Si grains produced wide PL in the range of 1.2-2.8 eV at room temperature. The PL was seen to be strongly dependent on the presence of the silicon oxide phase in the grain boundary and the crystalline volume fraction of the nc-Si grains. (C) 2012 Elsevier B.V. All rights reserved.